APPLICATION AND IMPROVEMENT PERFORMANCE OF PCB BOWTIE ANTENNA WITH LUMPED ELEMENT FOR PARTIAL DISCHARGE DETECTOR - WAHYU SHOPIYUDIN, ASEP
Partial discharge (PD) diagnosis with ultra high frequency (UHF) method has been developed with various varied geometric shapes to detect electromagnetic waves emitted on high voltage equipment due to PD activities. PD measurement using the UHF method is to measure the waves caused by the partial discharge which will propagate from the source of the PD out of the insulating material. EM wave propagation generated by PD can be detected using sensors, one of them is an antenna. In this research there are three new designs of bowtie antennas. The design of the first bowtie antennas is reference dimensions. The design of the second bowtie antennas is RC series. The design of the third bowtie antennas is RC parallel. The antenna is designed with FR4 epoxy substrate which has dimensions of diameter 90 mm, thickness is 1.6 mm. Antennas are designed in the frequency range of 50 MHz - 4 GHz. 3D-CST STUDIO SUITE software is used to design antennas. The antenna that has been designed is then implemented on printed cicuit board (PCB) material and measured using a vector network analyzer (VNA) to determine the antenna parameter characteristics. Antenna characteristic parameters which include return loss (RL), bandwidth and VSWR show the corresponding results based on the simulation results and measurement results. The three antenna designs have RL values L -10dB and VSWR ? 2. Testing of bowtie antennas for detecting PD in air and isolation using plate-needle electrodes. PD test results show the design of the bowtie antenna with RC series modification has good sensitivity in detecting PD compared to another bowtie antenna. In addition, the bowtie antenna RC series modification has a wide bandwidth value when compared to another bowtie antenna.